The impact of political instability on the tourism industries of selected Mediterranean destinations: a neural network approach - Theocharous, Antonis L. (My University, 2004)
This chapter investigates the impact of political instability on the tourist industries of four eastern Mediterranean destinations (Cyprus, Greece, Turkey and Israel) during the period 1977-97. It does so by producing a neural network model that enables an evaluation of the relationship between political instability and tourism. The results of the neural network confirm the current opinion that events of political instability can have a strong influence on the tourist industry. The series of experiments revealed further details of the interrelationship between the political instability factors and the number of tourist arrivals. It is concluded that neural networks indeed have the analytical ability to provide accurate predictions and the flexibility to incorporate various forms and types of independent variables that might be present in a tourism demand function.
Keywords: tourism industry; Mediterranean destinations; Tourism; governance